Tracing the Late Quaternary coastal evolution of Central Kerala, India, around the lost ancient port Muziris using multi-proxy study of the sedimentary archives - Prasenjit Das; D. Padmalal; K.P.N. Kumaran; Ruta B. Limaye; S. Vishnu Mohan; Upasana S. Banerji; Ravi Bhushan (Quaternary Science Advances, 2024)
The Central Kerala coast in Southwest India serves as a valuable natural archive for studies of the Late Quaternary coastal evolution, palaeoclimate, and maritime trades. The coast is an archeologically and culturally significant region in South India, located in the mouth of the longest river in Kerala, the Periyar River. The riverbank of the Periyar at its mouth is believed to host the ancient port Muziris, whose remnants are found in the areas around where the Periyar River joins the Arabian Sea. Sea level oscillations and climate variabilities in the past have played a pivotal role in the destruction of the Muziris port. Recent excavations unearthed many artifacts from nearby areas of the river confluence; however, the exact location of the port remains unresolved. The present study is an attempt to trace out the coastal evolutionary processes and palaeoclimatic conditions that prevailed in the area during the Late Quaternary period using three drilled cores retrieved from this stretch of the coastal lands. A multi-proxy approach, combining geochemical, mineralogical, palynological, and geochronological tools was used in the study. The Holocene deposit in the study area is composed mainly of sand and clay-dominant sediments that fall within an age range of 1.1–8.1 cal kyr BP, whereas the underlying sedimentary sequence dates to a maximum of 31.5–37.9 cal kyr BP. The inorganic and organic elemental compositions, together with the textural and palynological attributes, indicate that Holocene sedimentation occurred here under fluctuating environmental conditions with significant changes in climate and sea level positions. The upper part of this section bears the signature of the humid depositional environment that prevailed during the Late Holocene when sand-dominated sediments were deposited and brought in under the influence of longshore drift. The sediments from the lower part of the section carry the signature of the Holocene transgression when deposition took place under submerged conditions with considerable marine influence but receiving significant terrestrial inputs. The study highlights the location of the historically significant lost ancient port of Muziris at Kodungallur near the mouth of the Periyar River. A three-fold evolutionary model proposed for the coastal segment revealed that the location of the Muziris port was part of the Periyar River near Kodungallur, as mentioned by the historians, and the settlement near Pattanam may be considered a satellite township of the ancient Muziris port.